2019
DOI: 10.1111/tpj.14349
|View full text |Cite
|
Sign up to set email alerts
|

The genome of cowpea (Vigna unguiculata [L.] Walp.)

Abstract: SummaryCowpea (Vigna unguiculata [L.] Walp.) is a major crop for worldwide food and nutritional security, especially in sub‐Saharan Africa, that is resilient to hot and drought‐prone environments. An assembly of the single‐haplotype inbred genome of cowpea IT97K‐499‐35 was developed by exploiting the synergies between single‐molecule real‐time sequencing, optical and genetic mapping, and an assembly reconciliation algorithm. A total of 519 Mb is included in the assembled sequences. Nearly half of the assembled… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
222
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 263 publications
(244 citation statements)
references
References 85 publications
10
222
0
1
Order By: Relevance
“…Gene movements could be the result of double-strand break (DBS) repair through synthesis-dependent strand annealing mainly caused by transposable element activity (Wicker et al 2010). The class II transposons, which are the major group of classical cut-and-paste transposons, comprise 6.1% of the cowpea genome (Lonardi et al 2019). Chromosome synteny analysis between cowpea and its close relatives V. angularis, V. radiata and P. vulgaris revealed that chromosome 1 and 5 display rearrangements specific to the genus Vigna (Lonardi et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Gene movements could be the result of double-strand break (DBS) repair through synthesis-dependent strand annealing mainly caused by transposable element activity (Wicker et al 2010). The class II transposons, which are the major group of classical cut-and-paste transposons, comprise 6.1% of the cowpea genome (Lonardi et al 2019). Chromosome synteny analysis between cowpea and its close relatives V. angularis, V. radiata and P. vulgaris revealed that chromosome 1 and 5 display rearrangements specific to the genus Vigna (Lonardi et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The class II transposons, which are the major group of classical cut-and-paste transposons, comprise 6.1% of the cowpea genome (Lonardi et al 2019). Chromosome synteny analysis between cowpea and its close relatives V. angularis, V. radiata and P. vulgaris revealed that chromosome 1 and 5 display rearrangements specific to the genus Vigna (Lonardi et al 2019). In V. angularis and V. radiata , the ancestral CENH3 locus is conserved suggesting that CENH3 movement only occurred in some Vigna species during the rearrangement of chromosomes likely together with the activation of transposable elements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations